Community Economic Development Strategy Through Sago Development in Indragiri Hilir District - Syarifuddin, Said; lamin, lamin (ADPEBI, 2022)
Abstract Sago has an important meaning for the people of Indragiri Hilir Regency, both as a source of food in times of difficulty in getting rice and now and in the future that can be managed and developed as an alternative food source. Besides being able to be processed into food sources, sago can also be used as industrial raw materials. Indragiri Hilir Regency is very suitable for sago plants because its lowland area is peaty and drained by several rivers. However, until now there is no industry that processes it into finished goods. The purpose of this study is to develop a strategy for the Regional Government in developing a sago-based community economy, which is expected to be able to build downstream industries that produce finished goods. The method used in this study is a System Literature Review, to identify, evaluate, and interpret all journal articles and strategies for sago-based economic development. The results of the study found sago management strategies and development patterns through development programs through related OPDs and establishing cooperation with companies both local and outside the region in the short term and exports for the long term.